2022
DOI: 10.3389/fpsyg.2022.899936
|View full text |Cite
|
Sign up to set email alerts
|

Does Environmental, Social, and Governance Drive the Sustainability of Multinational Corporation’s Subsidiaries? Evidence From Korea

Abstract: We examined the relations between environmental, social, and governance (ESG) activities and the performance of subsidiaries of multinational corporations (MNCs). We further investigated the moderating effect of market-oriented organizational culture on the relationship between ESG and performance. Employing generalized least square regression analysis using survey data, we show that ESG activities of MNC subsidiaries are positively associated with financial and non-financial performance. These results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Our findings also hold important practical implications. Civic education programs may put an emphasis on credibility assessment and digital literacy (Kim et al, 2023;Metzger et al, 2010;van Deursen et al, 2016) given the potentially fruitful civic outcomes resulting from the interplay of active portal use and portal credibility.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also hold important practical implications. Civic education programs may put an emphasis on credibility assessment and digital literacy (Kim et al, 2023;Metzger et al, 2010;van Deursen et al, 2016) given the potentially fruitful civic outcomes resulting from the interplay of active portal use and portal credibility.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating social performance requires examining a company's policies, initiatives, and impact on various stakeholders. By emphasizing fair and ethical practices, social criteria contribute to a company's reputation and stakeholder trust (Kim et al, 2022).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…When looking for the relationship between the implementation of the ESG criteria and the corporate sustainability, the literature presents a heterogeneous scenario. Some researchers advocate a positive relationship (Harymawan et al, 2022;Kim et al, 2022), and others have confirmed a negative relationship (Rajesh and Rajendran, 2020).…”
mentioning
confidence: 99%